LAW ENFORCEMENT AGAINST WILD LEVELS CONDUCTED BY COMMUNITY ORGANIZATIONS IN THE LEGAL REGION OF THE POLRES OF BULELENG - I Gusti Ayu Agung Tri Wijayanthi; Ni Putu Rai Yuliartini; Dewa Gede Sudika Mangku (Jurnal Pendidikan Kewarganegaraan Undiksha, 2020)
This study aimed to determine and analyze law enforcement against extortion carried out bycommunityand to find out law enforcement efforts in tackling extortion in the Law Area of Buleleng Police Station. The type of this research was used is empirical legal research. This study usedqualitative descriptive with the location of this study carried out in several places namely in the Buleleng Police Station, the Buleleng District Attorney, Singaraja District Court, Buleleng Inspectorate and several shops in Buleleng. Data collection techniques were carried out using document studies, observations, and interviews. The results showed that (1) law enforcement apparatus in enforcing extortion cases carried out by community have been acted properly and decisively because law enforcers have the right to process and up to now there are no extortion in the community, (2) prevention efforts what has been done by law enforcement officers was in the form of preventive, Pre-emtive, and Represive actions